Africa and jus cogens: an ambivalent relationship - (:unkn) unknown (My University, 2022)
This article analyzes the contribution of Africa to the materialization and evolution of jus cogens , the normative standard codified in 1969 in the Vienna Convention on the Law of Treaties. The notion of jus cogens found an audience with African countries as soon as it appeared, thus allowing them to denounce the shortcomings of colonization as well as the international law relating thereto. Subsequently, and because of its repressive implications, it received contrasting application even from the states that had weighed in favour of its adoption. This fragile harmony has led to the conclusion that Africa maintains conflicted relations with jus cogens , which is perceived as undermining its sovereignty.
Keywords: African Research